Using Mobile Technology in Continuing Nursing Education - Yuni Susiana Nur; Tuti Nuraeni (Poltekkes Kemenkes Semarang, 2020)
Background: The development of technology after the industrial revolution, digital technology has brought changes in many aspects of life. Nurses as professionals who must always maintain and enhance their knowledge and skills are expected to be able to take advantage of the development of digital technology for the development of professionalism. This article presents a literature review that will explore the use of digital technology in Continuing Nursing Education.Purpose: The purpose of this research is to find out whether Continuing Professional Education can use digital technology.Methods: This type of research uses the PICO research tool (population, intervention, comparison, outcome) which is part of the literature review. The question used is whether the use of mobile technology by nurses can be applied in Continuing Professional Education activities.Results: Research with this literature review shows that the use of digital technology in Continuing Nursing Education is a transformation of the professional learning model that is very possible in professional nursing practice.Conclusion: The use of digital technology in contemporary nursing practice for the purpose of learning and teaching and expanding knowledge is made possible through the transformation of digital knowledge in real time at work. There needs to be readiness from individual nurses, systems, and organizations to be able to optimize the use of digital technology in Continuing Nursing Education.